Juridic Analysis Of Good Faith Inlimited Company Management - Khalid, Afif (International Journal of Educational Research & Social Sciences, 2022)
The Board of Directors is one of the organs of the Limited Liability Company in charge of managing the Company. For this reason, Law Number 40 of 2007 stipulates that the board of directors in managing the Company must have good intentions. However, the law does not determine and formulate the meaning of good faith, so legal certainty is needed. This research uses normative legal research, namely research on secondary data in the form of primary, secondary, and tertiary legal materials. The legal materials were obtained through literature study. Then the secondary data is processed and analyzed descriptively qualitatively. The results of the study show that first, the meaning of good faith in the management of the company by the directors based on the opinion of M. Yahya Harahap, among others, is being honest, referring to the aims and objectives of the company, as well as laws and regulations and being loyal to the company. Second, every member of the board of directors who does not have good intentions in managing the company is personally responsible for the company's losses.